Assessment of the knowledge of quality control among the personnel of a tertiary care hospital's biochemistry laboratory - Pallavi Mahajan; Ashima Badyal; Ruhi Mahajan (Current Medicine Research and Practice)
Background and Aims: Clinical laboratories are essential for disease screening, diagnosis and management, and they play a crucial role in patient care services. Thus, laboratory personnel’s primary responsibility is to issue high-quality reports that fulfil clinicians’ and patients’ expectations. Quality control (QC), including internal and external QC (IQC and EQC), is vital for the reliability of laboratory reports. QC encompasses the procedures used to determine whether laboratory results are reliable for clinical use, whereas IQC ensures daily consistency in the laboratory results. The aim of the study was to find out the knowledge of quality control both internal and external among laboratory personnel working in the Department of Biochemistry in a tertiary care centre. Materials and Methods: This study assessed the knowledge of QC among laboratory personnel working in the department of biochemistry in a tertiary care centre. A structured questionnaire was used to evaluate both IQC and EQC. Results: It was observed that 32% of laboratory personnel attained an average score, whereas 68% achieved a good score. Conclusions: The primary responsibility of laboratory personnel is to ensure accurate laboratory test results. Thus, the knowledge and practice of QC procedures improve medical laboratories’ quality and prepare laboratory personnel for various accreditation procedures.